The Role of Emotion‐Driven Impulse Control Difficulties in the Relation Between Social Anxiety and Aggression. Issue 6 (1st August 2016) - Dixon, Laura J.; Tull, Matthew T.; Lee, Aaron A.; Kimbrel, Nathan A.; Gratz, Kim L.
Abstract : Objectives: To enhance our understanding of the factors that may account for increased aggression in socially anxious individuals, this study examined associations among emotion‐driven impulse control difficulties, social anxiety, and dimensions of aggression (i.e., hostility, anger, physical aggression, verbal aggression). Method: Individuals ( N = 107; 73.8% male; Mage = 40.8 years) receiving residential substance abuse treatment participated in this cross‐sectional study. Results: Social anxiety symptoms were significantly positively correlated with emotion‐driven impulse control difficulties, anger, and hostility, but not verbal or physical aggression. Separate models for each aggression facet were examined to test the direct and indirect paths. Bootstrapped mediation analyses indicated a significant indirect path from social anxiety symptoms to each facet of aggression through emotion‐driven impulse control difficulties ( p s < .05). Conclusion: Results highlight the potential utility of targeting emotion‐driven impulse control difficulties to decrease aggression among socially anxious individuals.